ASKETISME SEBAGI FAKTOR PENDORONG PERNIKAHAN Studi tentang Pernikahan Mahasiswa Berhijab Syar’i - Fauziyah, Umi Nur; Suhartini, Elly (Jurnal ENTITAS SOSIOLOGI, 2019)
Asceticism is one of the challenges that must be faced by the world to get blessed to be closer to His heaven. The attitude of asceticism can motivate oneself to get married at a young age. Marriage is often interpreted as human nature to be something very crucial for humans themselves. Where humans are noble creatures on this earth, of course, must undergo this nature. The theory used is a social construction that was triggered by Peter L. Berger and Thomas Luckman. This study uses qualitative research methods with a constructivism approach. The results of the study showed that asceticism was the main factor that led to the occurrence of marriage among female students of syar'i. Another thing that can be categorized into asceticism is obedience to parents, obedient to husbands, happy, norms and rizq that are obtained. Besides, there are also dynamics in decision making for marriage and other factors that encourage the occurrence of marriage, namely, religious activities, socio-cultural and compliance with parents. The decision to get married chosen by the student has a positive and negative impact on the life being lived both in the academic field and in everyday life. Keywords: Asceticism, Students, Marriage.